A sacred oath ebook Memoirs of a secretary of defense during extraordinary times. - Esper, Mark T. (2022)
INSTANT NEW YORK TIMES BESTSELLER Former Secretary of Defense Mark T. Esper reveals the shocking details of his tumultuous tenure while serving in the Trump administration. From June of 2019 until his firing by President Trump after the November 2020 election, Secretary Mark T. Esper led the Department of Defense through an unprecedented time in history—a period marked by growing threats and conflict abroad, a global pandemic unseen in a century, the greatest domestic unrest in two generations, and a White House seemingly bent on breaking accepted norms and conventions for political advantage. A Sacred Oath is Secretary Esper's unvarnished and candid memoir of those extraordinary and dangerous times, and includes events and moments never before told.